Evaluation partial substitution of fresh forage with silage on dairy milk production in Kunak which added palm kernel meal and Gracilaria sp on daily feed - Agustin Herliatika; Idat Galih Permana; Despal Despal (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2020)
Kunak is the biggest community for a traditional dairy cattle farmer in West of Java. Providing good qualities and quantities of forage continuously in a year for ruminants, still be one problem in this community caused by different forage production between the dry season and rainy season. High forage production in the rainy season could be stored as silage to provide forage requirement in the dry season. These research examined in 2 experiments. The first experiment aimed to determine the effect partial-substitute of fresh forage uses grass silage on the quantities and qualities of daily milk production. The second experiment aimed to determine the quantities and qualities of dairy cattle milk production, affected by adding Gracilaria sp (GS) on partial-substitute of fresh forage uses grass silage and palm kernel-meal (S-PKM) on daily feed. These research uses complete randomized design divided into two treatments (to substitute as much as 0% and 10.08% Dry matter of fresh forage with grass silage) with five replications on the first experiment and three treatments (0%S-PKM-0%GS; 19.51%S-PKM-0%GS; 15.03%S-PKM-2.03%GS) with three replications on the second experiment. The results showed that substituting as much as 10.08% DM of fresh forage uses grass silage does not affect the feed intake (11.56-11.98 Kg DM/head/day), Feed Digestibility (59.37-63.45%), milk protein-production (0.36-0.37 Kg/head/day), milk fat-production (0.54-0.58 Kg/head/day), daily milk production (12.36-12.67 Kg/head/day) in the first experiment. Feed intake (Kg DM /head/day), milk protein-production (Kg/head/day), milk fat-production (Kg/head/day), and daily milk production (Kg/head/day) increase with added 15.03%S-PKM-2.03%GS in the second experiment.